1994
DOI: 10.1029/94wr02046
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Picard and Newton iteration in the numerical solution of multidimensional variably saturated flow problems

Abstract: Picard iteration is a widely used procedure for solving the nonlinear equation governing flow in variably saturated porous media. The method is simple to code and computationally cheap, but has been known to fail or converge slowly. The Newton method is more complex and expensive (on a per-iteration basis) than Picard, and as such has not received very much attention. Its robustness and higher rate of convergence, however, make it an attractive alternative to the Picard method, particularly for strongly nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
242
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 302 publications
(245 citation statements)
references
References 26 publications
(12 reference statements)
2
242
0
1
Order By: Relevance
“…The subsurface flow module in CATHY solves the 3-D Richards equation describing flow in variably saturated porous media (Paniconi and Putti, 1994), while the surface flow module solves the diffusion wave equation describing surface flow propagation over hillslopes and in stream channels identified using terrain topography and the hydraulic geometry concept (Orlandini and Rosso, 1998). Surface-subsurface coupling is based on a boundary condition switching procedure that automatically partitions potential fluxes (rainfall and evapotranspiration) into actual fluxes across the land surface and calculates changes in surface storage.…”
Section: The Hydrological Modelmentioning
confidence: 99%
“…The subsurface flow module in CATHY solves the 3-D Richards equation describing flow in variably saturated porous media (Paniconi and Putti, 1994), while the surface flow module solves the diffusion wave equation describing surface flow propagation over hillslopes and in stream channels identified using terrain topography and the hydraulic geometry concept (Orlandini and Rosso, 1998). Surface-subsurface coupling is based on a boundary condition switching procedure that automatically partitions potential fluxes (rainfall and evapotranspiration) into actual fluxes across the land surface and calculates changes in surface storage.…”
Section: The Hydrological Modelmentioning
confidence: 99%
“…In their sensitivity analysis study of CATHY to the soil hydrodynamic properties, Muma et al [53] noticed that the saturated hydraulic conductivity of the deeper layers (fifth group of layers) had a significant impact on to drain discharge and outlet of the micro-watershed flow. Furthermore, they revealed that the vertical saturated hydraulic conductivity in the two surface layers (first group of layers) as well as the vertical and lateral saturated hydraulic conductivity in the layers where the subsurface drains are located deserved special attention due to their strong interaction with other parameters with regards to drain discharge.…”
Section: Layer Numbermentioning
confidence: 99%
“…Isotropic and anisotropic properties of soil saturated hydraulic conductivity (*) analysed. In their sensitivity analysis study of CATHY to the soil hydrodynamic properties, Muma et al [53] noticed that the saturated hydraulic conductivity of the deeper layers (fifth group of layers) had Notes: * All hydraulic conductivity values are expressed in m/s. In each column, the value on the left of the slash is the horizontal hydraulic conductivity (X and Y), while the value on the right is the vertical hydraulic conductivity (Z).…”
Section: Layer Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling of water flow in unsaturated porous media is usu-, ally based on Richards' equation [Richards, 1931], and with a few exceptions, existing numerical models use Picard or Newton iteration [Paniconi and Putti, 1994]. Iteration-to-iteration oscillation often arises and causes slow convergence or failure to converge, especially when simulating large and rapidly changing infiltration flows .…”
mentioning
confidence: 99%